2019
DOI: 10.1002/jbio.201900122
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐brain microcirculation detection after ischemic stroke based on swept‐source optical coherence tomography

Abstract: The occurrence and development of ischemic stroke are closely related to cerebral blood flow. Real‐time monitoring of cerebral perfusion level is very useful for understanding the mechanisms of the disease. A wide field of view (FOV) is conducive to capturing lesions and observing the progression of the disease. In this paper, we attempt to monitor the whole‐brain microcirculation in middle cerebral artery occlusion (MCAO) rats over time using a wide FOV swept‐source OCT (SS‐OCT) system. A constrained image re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…In our previous study, 22 we found that blood flow immediately decreased after ET-1 injection. But, at this time, OAC did not change significantly.…”
Section: -5mentioning
confidence: 64%
See 2 more Smart Citations
“…In our previous study, 22 we found that blood flow immediately decreased after ET-1 injection. But, at this time, OAC did not change significantly.…”
Section: -5mentioning
confidence: 64%
“…A wide FoV SS-OCT system, set up in our previous work, 31 was used in this study, as shown in Fig. 1.…”
Section: Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide-range SS-OCT system was selected for the experiments [37]. The light source used is a swept-source with a center wavelength of 1310 nm and a bandwidth of 100 nm.…”
Section: Ss-oct Systemmentioning
confidence: 99%
“…In this article, an image registration algorithm based on constrained demons introduced in our previous research was used [32]. In this article, an image registration algorithm based on constrained demons introduced in our previous research was used [32].…”
Section: Motion Artifact Eliminationmentioning
confidence: 99%